Two decades of evaluation of processing tomato cultivars in Portugal: Programmes Meti, Metiber AND EC- Amiton Trials - Machado, Rui (1994)
ISHS Acta Horticulturae 376: V International Symposium on the Processing Tomato TWO DECADES OF EVALUATION OF PROCESSING TOMATOES CULTIVARS IN PORTUGAL: PROGRAMMES METI, METIBER AND EC-AMITON TRIALS Authors: R.M.A. MACHADO, M.L. TABORDA, A.M. CALADO, C.A.M. PORTAS Abstract: The aim of this presentation is to report on experiments that have been done in Portugal from 1970 to date and also to describe the behaviour of tomato cultivars over this period, evaluated both for their agronomic and technological features. Cultivars were ranked on the basis of agronomic and technological evaluation following methodology adapted from the SONITO procedures. The best five cultivars in each year and their most important characteristics - yield, °Brix, and soluble solids (t/ha) - are presented.